Inovasi Insektisida Organik Berbahan Eco Enzyme Untuk Penguatan UMKM Pertanian – LPPNU Tani Sejahtera - Wahyuni Ningsih; Noor Isnaini Azkiya; Anugrah Windy Mustikarini; Lintang Alivia Anggerta; Ariani; Zakijah Irfin (PELITA NUSA TENGGARA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the agricultural sector face challenges in implementing environmentally friendly and cost-effective pest control. The use of synthetic pesticides has negative impacts on health and the environment. This community service activity aims to enhance farmers’ knowledge and skills in producing organic insecticides made from eco-enzyme as an alternative to synthetic pesticides. The activity was carried out in three stages: preparation (equipment and materials setup, communication material design, and evaluation instrument development), implementation (socialization, demonstration, and hands-on practice), and post-implementation (evaluation and dissemination). The effectiveness was evaluated using pretest-posttest and participant satisfaction questionnaires. The results showed a significant increase of 150% in participants’ knowledge, from an average score of 26.67 to 66.67. The satisfaction questionnaire indicated that 84% of respondents gave positive feedback on the activity. The training program successfully improved MSMEs’ capacity in producing organic insecticides and provided an environmentally friendly alternative solution for pest control.